Iron Promotes Dihydroartemisinin Cytotoxicity via ROS Production and Blockade of Autophagic Flux via Lysosomal Damage in Osteosarcoma - Shen, Ying; Zhang, Bin; Su, Yanwei; Badshah, Shaikh Atik; Wang, Xiaofei; Li, Xin; Xue, Yanru; Xie, Li; Wang, Zhe; Yang, Zhouqi; Zhang, Ge; Shang, Peng (Frontiers in Pharmacology, 2020)
Osteosarcoma cellular iron concentration is higher than that in normal bone cells and other cell types. High levels of cellular iron help catalyze the Fenton reaction to produce reactive oxygen species (ROS), which promotes cancer cell proliferation. Dihydroartemisinin (DHA), a classic anti-malarial drug, kills plasmodium through iron-dependent ROS generation. In this research, we observed the anti-osteosarcoma effects and mechanisms of DHA. We found that DHA induced ROS production, caused mitochondrial damage ，and activated autophagy via stimulation of the ROS/Erk1/2 pathway. As the storage site for a pool of ferrous iron, lysosomes are often the key organelles affected by drugs targeting iron. In this study, we observed that DHA induced lysosomal superoxide production, leading lysosomal membrane permeabilization (LMP) and autophagic flux blockage. By reducing or increasing cellular iron using deferoxamine (DFO) or ferric ammonium citrate (FAC), respectively, we found that DHA inhibited osteosarcoma in an iron-dependent manner. Therefore, iron may be a potential adjuvant for DHA in osteosarcoma treatment.